Prediabetes and Their Contributed Factors: A Study in Semarang - Kusumaningrum, Niken Safitri Dyan; Hidayati, Wahyu; Muin, Muhammad (Jurusan Keperawatan FIKES UNSOED, 2020)
Background. Prediabetes is a condition when blood glucose levels are above normal but do not yet meet the criteria for diabetes mellitus. Many people have already been diagnosed with prediabetes. However, there is little data that shows the prevalence and characteristics of people with prediabetes.Objective. To identify the prevalence and demographic characteristics of adults with prediabetes in Semarang, Central Java, Indonesia.Method. A cross-sectional study conducted in 21 Puskesmas (public health centers) in Semarang which were randomly selected from a total of 37 Puskemas. Out of 123 respondents participating in this study, 105 respondents met the inclusion criteria of the study. Oral Glucose Test Tolerance (OGTT) was done after peripherally screening for random glucose levels. Univariate analysis was performed to calculate the frequency and percentage of each variable.Results. The result shows that the prevalence of adult respondents with prediabetes in this study accounted for 17.14%. This study also found that the respondents’ mean age was 38.57 ± 14.84. The majority of the respondents were women (66.7%). They have normal BMI, yet higher waist circumference (23.82 ± 4.48; 83.13 ± 11.34), respectively.Conclusion. Prediabetes is prevalent among adults in Semarang. Thus, to control the incidence of uncontrolled DM, screening needs to be done to identify individuals with prediabetes in order to prevent it from developing into DM. In addition, the application of healthy lifestyle interventions among adults at risk of diabetes also needs to be improved.